Wilhelm Dilthey's Hermeneutical Methodology in Understanding Text - Umaruddin Nasution (Kawanua International Journal of Multicultural Studies, 2022)
The research aims to describe the methodology of hermeneutics Wilhelm Dilthey in understanding text. Dilthey was a philosopher who played an important role in developing hermeneutics as a scientific methodology. The study used library research which guides the hermeneutic books and other documents that give explanations of their thinking. This research also used a historical-philosophical approach and content analysis. The results of this study indicate that Dilthey thought of hermeneutics has three formulations in which the text’s interpretation is experience, expression, and understanding. Dilthey's hermeneutics methodology is a process of interpreting text by understanding the author's history, which manifests into a text, language, and discourse.